Non-pharmacotherapeutic atmiatrics with combined mud medication «Tone plus» in pulmonology - T. N. Zaripova; I. N. Smirnova; V. S. Moskvin; I. I. Antipova (Бюллетень сибирской медицины)
The aim of investigation: to ground the use of a new combined mud medication «Tone plus» in pulmonologic practice. The investigation has been made on 53 patients with chronic bronchitis (CB) and bronchial asthma (BA). Inhalations with «Tone plus» consisting of three components — saline carrier, herb and peloids extracts — have been the main medication. Efficiency of the therapy has been assessed grounding on the movement of local respiratory tract protection indices by the method of examination of nasal tunica mucosa smear and nasal secretion, on the airway conductance by spirograph, inflammation activity by blood clinico-biochemical analysis and on organism adaptation system state by L.A. Garkavy’s method. In atmiatrics there has been registered local and system anti-inflammatory effect, airway conductance improvement and improvement of upper airway cover epithelium state, increase of functional activity of respiratory tract tunica micosa cells. Inhalations of a new combined mud medication «Tone plus» are a promising method of non-pharmacotherapeutic atmiatrics of patients with CB and BA.